2019
DOI: 10.1108/md-06-2017-0574
|View full text |Cite
|
Sign up to set email alerts
|

The weight of organizational factors on heuristics

Abstract: Purpose The purpose of this paper is to investigate the influence of organizational factors on individual decision-making under conditions of uncertainty and time pressure. A method to assess the impact of individual and organizational factors on individual decisions is proposed and experimented in the context of triage decision-making process. Design/methodology/approach The adopted methodology is based on the bias-variance decomposition formula. The method, usually applied to assess the predictive accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…For future study to further support the Time Pressure Mitigation Model, researchers could test whether time management and self-leadership practices improve psychosocial care in units with similar time pressure as emergency departments face. Given the literature on triage practices and decision making though (Mackway-Jones et al 1997;Bucknall 1999, 2001;Cone and Murray 2002;Barberà-Mariné et al 2019), triage decisions in an emergency department may be a good starting point for future empirical research. Yet, the model in this paper is not limited to nurse managers.…”
Section: Discussionmentioning
confidence: 99%
“…For future study to further support the Time Pressure Mitigation Model, researchers could test whether time management and self-leadership practices improve psychosocial care in units with similar time pressure as emergency departments face. Given the literature on triage practices and decision making though (Mackway-Jones et al 1997;Bucknall 1999, 2001;Cone and Murray 2002;Barberà-Mariné et al 2019), triage decisions in an emergency department may be a good starting point for future empirical research. Yet, the model in this paper is not limited to nurse managers.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on factors affecting nurses' decisionmaking in Triage highlights contextual factors and individual nurse's experience, knowledge, and intuition can cause the variation of nurses' decision-making in assessing patient urgency [36][37][38] and the weight of organizational and individual factors can vary according to task complexity. 18 In addition, given the characteristics of Triage process, the quality of decisions depends also by the capacity of nurses to assign the same priority code to patients with similar urgency. Aside from the wrong priority code, the nurses can exhibit the capacity to discriminate patients according to the different urgency or, on the contrary, put together patients even if they exhibit different clinical conditions.…”
Section: Triage As Decision-making Based On Cognitive Heuristicsmentioning
confidence: 99%
“…15,16 The disparity also depends on nurses' interpretation process of patient's clinical conditions based on few cues, short time, and influenced by experience. 17 Previous research focused on analyzing the different intensity of organizational and individual factors on nurses' dynamic decision-making 18 and on the assessment of factors that affects the nurses' decision. 19 This paper aims at designing performance indexes for assessing the quality of nurses' decision and detecting the prevalence of shared behaviors among nurses in specific situations.…”
Section: Introductionmentioning
confidence: 99%
“…Guercini et al (2015) found that sharing “is mostly in the form of an informal exchange of opinions among close friendly colleagues.” Barberà-Mariné et al (2019, p. 2901) study triage heuristics followed by nurses and show that, in particular, training “acts as a medium to share informal rules among individuals.” Bingham et al (2019) document an informal process, as “knowledge sharing happened daily through informal conversations between managers” (p. 139), but emphasize the role of “extensive communication within and across multiple hierarchical levels” (p. 121). It should also be noted that collectively generated heuristics are born shared.…”
Section: Toward a Theory-based Process Model Of How Heuristics Emergementioning
confidence: 99%
“…Soft adoption occurs through informal communication and heuristics are adopted under the expert authority of the manager who shares them. As an example, during training, “experienced nurses can show beginners how to apply triage protocols for priority levels' assignment” (Barberà-Mariné et al , 2019, p. 2901). The application of a soft adopted heuristic is optional and the adopter is more likely to question, adapt, refine, change or abandon the heuristic.…”
Section: Toward a Theory-based Process Model Of How Heuristics Emergementioning
confidence: 99%